At-Tafsīru al-‘Ilmiyyi fī Miṣra al-Ḥadīṡati - Abdulaziz, Eid (Middle Eastern Culture & Religion Issues, 2025)
This study investigates the characteristics of scientific interpretation (tafsir ʿilmī) of the Qur'an in modern Egypt during the twentieth century by analyzing the contributions of prominent Egyptian exegetes who sought to correlate the Qur'anic text with contemporary scientific discoveries. The novelty of the research lies in its qualitative analytical framework that integrates hermeneutical theory with exegetical discourse, filling a critical gap left by previous studies that addressed the phenomenon in broad or narrow regional terms. Employing a qualitative interpretive methodology, the research uses semi-structured interviews and content analysis to examine three prevailing positions: rejectionist, moderate, and expansionist attitudes toward scientific exegesis. The findings reveal significant conceptual diversity among scholars in interpreting scientific references in the Qur'an, reflecting broader implications for the notion of miracle (iʿjāz) and religious epistemology. The study makes a substantial theoretical contribution by proposing a reconstructed model of scientific tafsir that harmonizes textual integrity with modern knowledge, and it outlines practical applications for educational and religious contexts. Ultimately, this work enhances the Qur'an's relevance in addressing contemporary scientific and philosophical challenges, affirming its dynamic capacity for engagement beyond traditional interpretive paradigms.